PENGARUH UKURAN PERUSAHAAN, NILAI PERUSAHAAN, FINANCIAL LEVERAGE, NPM DAN PROFITABILITAS TERHADAP PERATAAN LABA - Lauren, Anastasia; Nugroho, Vidyarto (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
The aim of the study was to examine the effect of firm size, firm value, financial leverage, net profit margin and profitability on income smoothing practices in manufacturing companies listed on the Indonesia Stock Exchange for the period 208-2020. From several sample selection criteria, 35 companies were selected by purposive sampling method that met the criteria. Processing research data using logistic regression analysis which is processed using SPSS (Statistical Product and Service Solution) edition 26. The results shows that company size, financial leverage, net profit margin and profitability have no effect on income smoothing, while firm value has a negative effect to income smoothing. The implication of this study is for investors to be more thorough and critical in assessing the company's performance, especially from the financial side in making investment decisions.